PICADAR: a diagnostic predictive tool for primary ciliary dyskinesia. Issue 4 (25th February 2016) - Behan, Laura; Dimitrov, Borislav D.; Kuehni, Claudia E.; Hogg, Claire; Carroll, Mary; Evans, Hazel J.; Goutaki, Myrofora; Harris, Amanda; Packham, Samantha; Walker, Woolf T.; Lucas, Jane S.
Symptoms of primary ciliary dyskinesia (PCD) are nonspecific and guidance on whom to refer for testing is limited. Diagnostic tests for PCD are highly specialised, requiring expensive equipment and experienced PCD scientists. This study aims to develop a practical clinical diagnostic tool to identify patients requiring testing. Patients consecutively referred for testing were studied. Information readily obtained from patient history was correlated with diagnostic outcome. Using logistic regression, the predictive performance of the best model was tested by receiver operating characteristic curve analyses. The model was simplified into a practical tool (PICADAR) and externally validated in a second diagnostic centre. Of 641 referrals with a definitive diagnostic outcome, 75 (12%) were positive. PICADAR applies to patients with persistent wet cough and has seven predictive parameters: full-term gestation, neonatal chest symptoms, neonatal intensive care admittance, chronic rhinitis, ear symptoms, situs inversus and congenital cardiac defect. Sensitivity and specificity of the tool were 0.90 and 0.75 for a cut-off score of 5 points. Area under the curve for the internally and externally validated tool was 0.91 and 0.87, respectively. PICADAR represents a simple diagnostic clinical prediction rule with good accuracy and validity, ready for testing in respiratory centres referring to PCD centres. PICADAR is a simple diagnostic prediction tool for PCD with good accuracy and validity that is now ready for testing http://ow.ly/X6y9s